MATHEMATICAL ANALYSIS AND STATISTICS - Maksetova Zuhra Kabulovna (Journals Park Publishing, 2023)
In the vast realm of mathematics, two pillars stand prominentlyMathematical Analysis and Statistics. These fields, while distinct in their focus, share an intertwined relationship that underpins their importance across various disciplines. As we delve into the intricate world of numbers, patterns, and data, a deeper understanding of mathematical analysis and statistics unveils their pivotal roles in shaping our comprehension of the world.
Keywords: Mathematics, patterns, numbers, Mathematical Analysis, Statistics, Mathematical Concepts, Limits, Continuity, Differentiability, Applications of Mathematical Analysis, Physics, Engineering, Economics, Statistical Methods.